Enamel Based Composite Layers Deposited on Titanium Substrate with Antifungal Activity - S. L. Iconaru; A. M. Prodan; C. S. Turculet; M. Beuran; R. V. Ghita; A. Costescu; A. Groza; M. C. Chifiriuc; P. Chapon; S. Gaiaschi; R. Hristu; G. A. Stanciu; et al. (Journal of Spectroscopy)
The goal of this paper was to investigate the antifungal activity of Enamel layers deposited on titanium substrate (Ti-Enamel) and Enamel layers deposited on titanium substrate previously coated with a vinyl polydimethylsiloxane layer (Ti-PDMS-Enamel). The physicochemical properties were also investigated. The Candida albicans biofilm development on the obtained layers was examined after 24 h, 48 h, and 72 h by confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM) after ethidium bromide staining. A significant inhibition of the fungal adherence and biofilm development was observed on Ti-Enamel layers. The antifungal results demonstrated that the use of new Ti-Enamel composite layers could represent a promising perspective for the prevention of fungal biofilms associated implant infections.